A qualificação do conceito assédio moral no Brasil : implicações nas práticas de gerenciamento do capital humano - Souza, Vera Lucia de (Universidade Federal de São Carlos, 2008)
What has changed regarding personnel management in Brazil since the nomination of the concept of moral harassment ? The search of an answer to this question induced the development of this doctorate thesis, which the subject is moral harassment and its purpose being the qualification of this concept in the country and its objective the investigation of its impact in managerial practices in Brazilian organizations. The work supported on the hypothesis that this nomination, transforming individual complaint in organizational phenomenon has provoked changes in the perception of Brazilian society. Consequently, the study focused on the analysis of the sources of its qualification, in the logic of transformation from individual complaint into organizational phenomenon, in the dynamic practices qualified as moral harassment, in the presuppositions of manipulation, in instruments of contemporary corporate justice and in fundaments for evaluating workers. The results were obtained from the analysis of empirical material, collected from written and electronic communications sources, for the periods between 1983 and 2006. The analysis has proved that the most relevant impact of creating this legal notion, in the Brazilian organizational scope, was the escalation of public denunciation from the year 2000 onwards, seeking indemnification for the damage caused by these managerial practices.
Keywords: Assédio moral; Fenômenos organizacionais; Denuncia pública; Qualificação do conceito assédio moral; Queixa individual; Qualification of moral harassment concept; Individual complaint; Organizational phenomenon; Public denunciation; ENGENHARIAS::ENGENHARIA DE PRODUCAO